Red and violet gahnite (spinel) occurrences in Ganesh Himal (central Nepal): their chemistry, inclusions and microthermometry - Uhlir, C. F.; Hasenberger, K.; Kirchner, E. C. (Journal of Nepal Geological Society, 1998)
The red and violet gahnites occur within dolomite marbles of medium grade amphibolite facies in the Ganesh Himal area, central Nepal. The dolomites are part of the Higher Midland Formation and lie at the northern limb's eastern end of the Kunchha-Gorkha anticline within the MCT zone of Le Fort (1975). Both gahnites (ZnAl2O4) show a chemical zonation with various contents of Cr, Mg and Fe. The red colour is most probably caused by chromium. The inclusions containing fluids have ideal negative crystal shapes or are irregular. Beside them, various solid inclusions are also found. The fluids of the two- or three-phase inclusions contain H2O and CO2 Two generations of inclusions varying in the content of CO2 indicate a trapping at different PT condition or a water loss of the high CO2 inclusions during some tectonic event.